Learning from mistakes in rational emotive behaviour therapy - Dryden, Windy; Neenan, Michael (London : Routledge, 2012)
'Mistakes are often an inevitable part of training; Learning from Mistakes in Rational Emotive Behaviour Therapy encourages the trainee to pinpoint potential errors at the earliest possible stage in training, helping them to make fast progress towards becoming competent REBT practitioners.Windy Dryden and Michael Neenan have compiled 111 of the most common errors, explaining what has gone wrong and how to put it right, and have divided them into eight accessible sections:general mistakesassessment mistakesgoal setting mistakesdisputing mistakeshomework mistakesdealing with client doubts, reservations and misconceptionsworking through mistakesself maintenance.Learning from Mistakes in Rational Emotive Behaviour Therapy is an indispensible guide for anyone embarking on a career in the REBT field'--
Keywords: Psychotherapy, Rational-Emotive.